A Probabilistic Analytical Seismic Vulnerability Assessment Framework for Substandard Structures in Developing Countries - Kyriakides, Nicholas; Ahmad, Sohaib; Pilakoutas, Kypros; Neocleous, Kyriacos; Chrysostomou, Christis (My University, 2014)
This paper presents a framework for analytical seismic vulnerability assessment of substandard reinforced concrete (RC) structures in developing countries. A modified capacity-demand diagram method is used to predict the response of RC structures with degrading behaviour. A damage index based on period change is used to quantify the evolution of damage. To demonstrate the framework, a class of substandard RC buildings is examined. Abrupt accumulation of damage is observed due to the brittle failure modes and this is reflected in the developed vulnerability curves, which differ substantially from the curves of ductile structures.
Keywords: Seismic vulnerability; Reinforced concrete; Sub-standard construction; Non-linear static; Damage index; Analytical; Probabilistic; Capacity-demand diagram methods